(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the theory of parts of the sentence, focusing on its three main components: principal, secondary, and tertiary parts. The principal parts subject and predicate—form the structural foundation of sentences, while secondary parts such as objects, complements, and adverbial modifiers add depth and detail. The article highlights the challenges posed by tertiary elements like appositions, interjections, and parenthetical expressions, which often defy strict categorization due to their fluidity and contextual significance. Beyond grammatical analysis, the article examines the broader implications of this theory for syntax, semantics, pedagogy, and computational linguistics.